From quarks and gluons to quantum gravity : proceedings of the International School of Subnuclear Physics - Zichichi, Antonino (Subnuclear series, 2003)
In August/September 2002, a group of 78 physicists from 50 laboratories in 17 countries met in Erice, Italy, to participate in the 40th Course of the International School of Subnuclear Physics. The purpose of the School was to focus attention on the theoretical and phenomenological developments in gauge theories, as well as in all the other sectors of subnuclear physics. Experimental highights from the most relevant sources of new data were presented and discussed, including the latest news on theoretical developments in quantizing the gravitational forces. This volume constitutes the procee.